The efficiency of rumen microbial nitrogen and biomass synthesis of some indigenous range plants using 15N-tracer technique - Al-Masri, Mohamad Rateb (Acta Scientiarum. Animal Sciences, 2024)
This study was performed to evaluate, by the use of in vitro incubation technique with ruminal liquid and 15N-tracer for 96 h, some perennial range plants (Artemisia herba-alba Asso, Noaea mucronata Forssk, Lavandula angustifolia Mill, Astragalus spinosus Forssk, Capparis spinosa L.) grown naturally on dry rangelands, in terms of rumen microbial nitrogen (M.N), microbial biomass (M.BM), true fermented organic matter (T.F.OM) and quantification of the efficiency of M.N and M.BM synthesis (M.N or M.BM / T.F.OM), and study the effect of polyethylene glycol (P.E.G) on the aforementioned parameters. C. spinosa had the highest (p < 0.05) values of T.F.OM, M.N and M.BM. Microbial N and M.BM values ranged from 0.57 to 0.82 mg g-1 DM and from 6.13 to 9.46 mg g-1 DM, respectively. There were no significant (p > 0.05) differences among plant species in terms of the efficiency of M.N and M.BM synthesis, and the average amounted to 0.282 g and 3.25 g 100 g-1 of truly fermented organic matter, respectively. M.BM and M.N values were negatively correlated with lignin but positively correlated with soluble nitrogen. P.E.G supplementation and the interaction between P.E.G treatment and plant species had no significant (p > 0.05) effect on the estimated parameters.